First Foods as Indigenous Food Sovereignty: Country Foods and Breastfeeding Practices in a Manitoban First Nations Community - Cidro, Jaime; Martens, Tabitha Robin; Zahayko, Lynelle; Lawrence, Herenia P. (Canadian Food Studies / La Revue canadienne des études sur l'alimentation, 2018)
As a concept and in practice, Indigenous food sovereignty (IFS) offers insights into the social, cultural, and environmental challenges of a deficient food system. The associated poor health outcomes of this system include infant and child health issues such as early childhood caries and childhood obesity, and are a grave concern in many First Nations communities. Extant research has failed to consider the role of infant feeding traditions as an element of Indigenous food sovereignty. Breastfeeding and country food (also called traditional food or cultural food) consumption among infants has been long practiced in First Nations communities, resulting in healthier infants. The research described in this article originated with a research project called the Baby Teeth Talk study (BTT). This is a community-based trial which is testing a pre-natal/post-natal behavioural and preventive intervention for early childhood caries (ECC) among pregnant First Nations women and their infants in urban and on-reserve communities in Ontario and Manitoba. In Norway House Cree Nation, located in northern Manitoba, research participants shared stories on the methods used by caregivers for oral health care, including breastfeeding promotion. This paper reviews the literature relating to IFS, breastfeeding, and the introduction of country food to infants. Through the voices of grandmothers in one community in northern Manitoba, Canada, we connect the introduction of country food and breastfeeding to the larger IFS movement and positive health outcomes for infants, and improve the conceptualization and practice of IFS. "This research was funded through the New Investigator Award for Aboriginal scholars through the Network Environment for Aboriginal Health Research (NEAHR) through the Canadian Institute of Health Research. We would like to acknowledge the support of the Manitoba NEAHR program in assisting with the logistics of this project. Funding was also provided through Northern Scientific Research Program." ...